Essentialism in Islamic Education: A Critical Examination of Thought and Its Relevance in the Modern Era - Aminudin (IAIN KENDARI, 2025)
This research aims to examine the relevance of the principles of essentialism in answering the challenges of contemporary Islamic education. The method used is library research with an analytical qualitative approach. Data were collected through documentation of primary literature, such as the works of William C. Bagley, E.D. Hirsch, Al-Ghazali, Al-Attas, and Al-Faruqi, as well as secondary literature in the form of Scopus and SINTA indexed journal articles, academic books, and dissertations published between 2020 and 2025. The results show that essentialism has a strong relevance in strengthening the foundation of Islamic education, especially in the aspects of values, basic knowledge, and character building. The principles of essentialism are in line with the core values of Islamic education such as ta'dīb, tarbiyah, and ta'līm, and are reflected in the practice of traditional education in pesantren and the integrative curriculum in madrasah. In the context of globalization and digitalization, essentialism also acts as a value filter and philosophical foundation that maintains a balance between technological mastery and spiritual moral formation. The discussion reinforces the finding that essentialism does not contradict the progress of the times, but rather becomes an adaptive and profound conceptual framework. Essentialism can be used as a philosophical paradigm in the reformulation of sustainable Islamic education that is not only responsive to change, but also steadfast in maintaining the value orientation and Islamic identity of students.